Acute changes in mitral valve geometry after percutaneous valve repair with MitraClip XTR by three‐dimensional echocardiography. Issue 11 (9th November 2021) - Tusa, Maurizio B.; Barletta, Marta; Popolo Rubbio, Antonio; Travaglio, Nicole; Saffioti, Silvia; Granata, Giuseppina; Mantovani, Valentina; Stefanini, Elisa; Corciu, Anca I.; Testa, Luca; Bedogni, Francesco
Abstract: Background: Mitral valve (MV) repair with MitraClip system is a safe treatment option for high‐risk patients with significant mitral regurgitation (MR). We aimed to characterize, by three‐dimensional echocardiography (3D‐E), changes occurring in MV after implantation of third generation MitraClip XTR device, with specific reference to the underlying MR mechanism (functional vs degenerative, FMR vs DMR). Methods: We prospectively enrolled 59 patients, who underwent intra‐procedural 3D‐E before and after device deployment. Three‐D datasets were analyzed off‐line, using a dedicated semiautomatic software, to obtain parametric quantification of mitral anatomy. Results: Post‐procedural MR of mild or lesser degree was achieved in 40 patients (68%), with no differences between FMR and DMR ( p 0.9). After MitraClip XTR implantation, the FMR group experienced an immediate annular resizing, with reduction of antero‐posterior diameter ( p 0.024) and sphericity index ( p 0.017), next to a recovery of physiological saddle‐shape, defined by lower non‐planar angle (p ≤0.001) and higher annulus height to commissural width ratio ( p ≤0.001). On the opposite, the DMR group revealed a significant decrease of maximum annular velocity ( p 0.027), addressing a mechanic effect of the device deployment. Finally, baseline anterior mitral leaflet angle was found as an independent predictor of acute procedural result (OR 6.7, [CI 1.01–44.33], p 0.049). Conclusions: MitraClip XTR implantation acts in restoring the original mitral geometry, with distinctive effects according to MR mechanism. Three‐D parametric quantification of MV sheds new light on changes occurring in the valvular apparatus, and helps identifying possible new predictors of acute procedural success.